COMPARACAO DE METODOLOGIAS CFD DE SIMULACAO DE TURBINAS HIDROCINETICAS - Mendes, Rafael Castilho Faria; Macias, Marianela Machuca; Silva, Paulo Augusto Strobel Freitas; Oliveira, Taygoara Felamingo de; Brasil Junior, Antonio Cesar Pinho (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The recent advances in technologies turned able that a computer provides a numerical simulation of fluid flows, well known as Computational Fluid Dynamics (CFD) technique. It means that the physical laws that govern the fluid behavior is in a “virtual” environment, where we can visualise the whole prototype system, such as a turbine, and how it works with great levels of realism. For many reasons, such as turbulence level and computational resource available, it is often impossible to describe the entire system with its all details. Consequently,we simplify the problem as much as possible to achieve the solution. In this sense, the aim of this work is to assess two different methodologies of CFD simulations of a 3 blade hydrokinetic turbine: full rotor and just one blade with symmetry simplification. As a result of it, the simulation of one blade rotor showed similar values of torque and pressure coefficient with the full rotor case.Thereby, this simplification presented the same level of results with a third of mesh.